Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Certainly! Let's break down the equation [tex]\(243^{-y} = \left(\frac{1}{243}\right)^{3y} \cdot 9^{-2y}\)[/tex] step-by-step.
1. Rewrite the equation with common bases:
- Notice that [tex]\(243 = 3^5\)[/tex] and [tex]\(9 = 3^2\)[/tex].
- Therefore, we can rewrite each term in the equation using base 3.
2. Convert to base 3:
- [tex]\(243^{-y} = (3^5)^{-y} = 3^{-5y}\)[/tex]
- [tex]\(\left(\frac{1}{243}\right)^{3y} = (243^{-1})^{3y} = (3^{-5})^{3y} = 3^{-15y}\)[/tex]
- [tex]\(9^{-2y} = (3^2)^{-2y} = 3^{-4y}\)[/tex]
3. Substitute these back into the original equation:
- [tex]\(3^{-5y} = 3^{-15y} \cdot 3^{-4y}\)[/tex]
4. Simplify the right-hand side:
- When multiplying powers with the same base, add the exponents: [tex]\(3^{-15y} \cdot 3^{-4y} = 3^{-15y + (-4y)} = 3^{-19y}\)[/tex]
5. Equate the exponents:
- We now have [tex]\(3^{-5y} = 3^{-19y}\)[/tex]
- Since the bases are the same, we can set the exponents equal to each other: [tex]\(-5y = -19y\)[/tex]
6. Solve for [tex]\(y\)[/tex]:
- Combine like terms: [tex]\(-5y + 19y = 0\)[/tex]
- Simplify: [tex]\(14y = 0\)[/tex]
- Divide by 14: [tex]\(y = 0\)[/tex]
Therefore, the solution is [tex]\(y = 0\)[/tex].
1. Rewrite the equation with common bases:
- Notice that [tex]\(243 = 3^5\)[/tex] and [tex]\(9 = 3^2\)[/tex].
- Therefore, we can rewrite each term in the equation using base 3.
2. Convert to base 3:
- [tex]\(243^{-y} = (3^5)^{-y} = 3^{-5y}\)[/tex]
- [tex]\(\left(\frac{1}{243}\right)^{3y} = (243^{-1})^{3y} = (3^{-5})^{3y} = 3^{-15y}\)[/tex]
- [tex]\(9^{-2y} = (3^2)^{-2y} = 3^{-4y}\)[/tex]
3. Substitute these back into the original equation:
- [tex]\(3^{-5y} = 3^{-15y} \cdot 3^{-4y}\)[/tex]
4. Simplify the right-hand side:
- When multiplying powers with the same base, add the exponents: [tex]\(3^{-15y} \cdot 3^{-4y} = 3^{-15y + (-4y)} = 3^{-19y}\)[/tex]
5. Equate the exponents:
- We now have [tex]\(3^{-5y} = 3^{-19y}\)[/tex]
- Since the bases are the same, we can set the exponents equal to each other: [tex]\(-5y = -19y\)[/tex]
6. Solve for [tex]\(y\)[/tex]:
- Combine like terms: [tex]\(-5y + 19y = 0\)[/tex]
- Simplify: [tex]\(14y = 0\)[/tex]
- Divide by 14: [tex]\(y = 0\)[/tex]
Therefore, the solution is [tex]\(y = 0\)[/tex].
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.